Basil A. Pruitt, Jr., MD, and the US Army Institute for Surgical Research: Five decades of science, clinical care, mentorship, and leadership. Issue 5 (November 2017) - Stewart, Ronald M.
Abstract : ABSTRACT: Over the past half century, Dr. Basil A. Pruitt, Jr., a great citizen, surgeon, innovator, mentor, and leader, transformed our world through his dogged commitment to science and service to humanity. Dr. Pruitt's contribution lives on in the work of the US Army Institute of Surgical Research and the surgeons, physicians and scientists he shaped and inspired.